THE RETENTION OF HINDU RELIGION IN THE CULTURAL VILLAGE OF KUTA - Adiputra, I Gede Rudia (E-Journal of Cultural Studies, 2016)
The discussion about the cultural village of Kuta as Global Village, cannot escape the discourse of Bali as the Global Island, it is because Bali Island has long been a global discourse so that it becomes an interesting place to be visited by tourists from all over the world. This raises a variety of concerns, particularly regarding the survival of Hinduism. To address that concern, Cultural village of Kuta felt the need to do something to Hinduism who stay in Bali. Likewise, Hinduism that permeates the culture of Bali that has been the main reason foreigners come to Bali. Thus, planting Sraddha and Bhakti becomes important to the community and remain as a top priority. On that basis, this work will show the factors that cause the retention of Hinduism in the cultural village of Kuta, the form of retention and the impact as well as the significance of the preservation.
Keywords: Retention, Hinduism, Cultural Village of Kuta, the culture of Bali.